Sistem Pemilihan Enam Menu Display pada Klinik menggunakan Pergerakan Kepala berbasis Nvidia Jetson Nano - Andika Kalvin Simarmata; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Based on the National Socio-Economic Survey (Susenas) in 2018, there were 30.38 million people with disabilities/14.2 percent of the total population in Indonesia. Persons with disabilities have difficulty operating electronic devices. On this basis, persons with disabilities need tools to operate these devices without physical contact. In addition, physical contact must also be minimized globally due to the COVID-19 pandemic which has spread throughout the world. The solution to this problem is to create a system that can operate electronic devices without making physical contact. This solution can be realized by using Facial Landmark-based head movements to select the display menu at the clinic with the application name